2016
DOI: 10.1103/physrevd.94.054019
|View full text |Cite
|
Sign up to set email alerts
|

Thermomagnetic properties of the strong coupling in the local Nambu–Jona-Lasinio model

Abstract: We study the thermo-magnetic properties of the strong coupling constant G and quark mass M entering the Nambu-Jona-Lasinio model. For this purpose, we compute the quark condensate and compare it to lattice QCD (LQCD) results to extract the behavior of G and M as functions of the magnetic field strength and temperature. We find that at zero temperature, where the LQCD condensate is found to monotonically increase with the field strength, M also increases whereas G remains approximately constant. However, for te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 40 publications
0
45
0
Order By: Relevance
“…The growth or decrease of the quark condensate would in turn be linked to the corresponding behavior of the coupling at zero or at high temperature, respectively. This scenario has been studied within effective QCD models [3][4][5][6][7][8][9], from the Schwinger-Dyson approach [10], and from the thermomagnetic behavior of the quark-gluon vertex in QCD [11,12]. In the latter, it has been shown that the growth or decrease of the effective QCD coupling, at finite temperature and magnetic field strength, comes from a subtle competition between the color charges of gluons and quarks in such a way that at zero temperature the former is larger than the latter, whereas at high temperature, the coupling receives contributions only from the color charge associated to quarks.…”
mentioning
confidence: 99%
“…The growth or decrease of the quark condensate would in turn be linked to the corresponding behavior of the coupling at zero or at high temperature, respectively. This scenario has been studied within effective QCD models [3][4][5][6][7][8][9], from the Schwinger-Dyson approach [10], and from the thermomagnetic behavior of the quark-gluon vertex in QCD [11,12]. In the latter, it has been shown that the growth or decrease of the effective QCD coupling, at finite temperature and magnetic field strength, comes from a subtle competition between the color charges of gluons and quarks in such a way that at zero temperature the former is larger than the latter, whereas at high temperature, the coupling receives contributions only from the color charge associated to quarks.…”
mentioning
confidence: 99%
“…Nevertheless, external magnetic field effects are best included through the Schwinger Proper-Time representation of the fermion propagator. This observation has been exploited to address the problem of magnetic catalysis [12] and inverse magnetic catalysis observed in lattice simulations [13,14] and confirmed by several approaches [7,8,15]. Under this environment, the effective coupling of the model can reach very large values, and therefore, exploring the validity of these regularization schemes in this super-strong coupling regime is a natural question to address.…”
Section: Introductionmentioning
confidence: 99%
“…[6] for a review) and its magnetized extension [7] from a complementary point of view of lattice [8] and other quantum field theoretical approaches [9,10]. Several regularization schemes have been used in literature within the context of NJL model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations